EFFECTIVENESS OF SUGAR EFFLUENT ON FIXEDFILM REACTOR WITH EFFECT OF VOLATALFATTY ACID (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Technological solutions allowing the increase of the technological efficiency ofanaerobic methods of wastewater treatment are still under investigation. The weaknessesof these solutions can be limited by the use of active fillings. As the capability of retainingmicroorganisms will act as biofilm factor influencing the performance of this reactor. Theaim of the present study was to determine the impact of fixed film reactor active fillingon the effectiveness of anaerobic treatment of sugar-industry effluent, the productionefficiency and the qualitative composition of the biogas produced. The effluent wasanalyzed with varying Organic Loading Rate (OLR) The OLR increased from0.031kgCOD/m3/day to 0.288kg COD/m3/day. With an average value of Volatile FattyAcid (VFA) of The Volatile Fatty Acid was at the maximum of 54mg/l to 24mg/l wascalculated by distillation method with five sets off COD concentrations. The maximumCOD removal efficiency of 86% along with production of 0.048m3/kgCOD of biogas at 3days Hydraulic Retention Time (HRT) was observed.